2016
DOI: 10.1016/j.jpeds.2016.06.053
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal Exposure to Magnesium Sulfate Is Associated with Reduced Cerebellar Hemorrhage in Preterm Newborns

Abstract: Objective To determine the association of antenatal magnesium sulfate with cerebellar hemorrhage in a prospective cohort of premature newborns evaluated by magnetic resonance imaging (MRI). Study design Cross-sectional analysis of baseline characteristics from a prospective cohort of preterm newborns (<33 weeks gestation) evaluated with 3T-magnetic resonance imaging (MRI) shortly after birth. Exclusion criteria were clinical evidence of a congenital syndrome, congenital infection, or clinical status too unst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 39 publications
4
47
0
3
Order By: Relevance
“…MgSO 4 administration was a protective factor for neonatal hypoglycemia in univariate analysis, but became non-significant in multivariate analysis. Antenatal MgSO 4 reduces incidence of cerebral palsy and hemorrhage in infants born preterm, regardless of total dose (19)(20)(21). MgSO 4 has been shown to decrease blood brain barrier permeability and increase plasma glucose concentration in a rat model of hypoglycemia (22).…”
Section: Discussionmentioning
confidence: 99%
“…MgSO 4 administration was a protective factor for neonatal hypoglycemia in univariate analysis, but became non-significant in multivariate analysis. Antenatal MgSO 4 reduces incidence of cerebral palsy and hemorrhage in infants born preterm, regardless of total dose (19)(20)(21). MgSO 4 has been shown to decrease blood brain barrier permeability and increase plasma glucose concentration in a rat model of hypoglycemia (22).…”
Section: Discussionmentioning
confidence: 99%
“…Functionally, WMI is associated with behavioral, cognitive, motor and psychological problems, like autism spectrum disorders (ASD), later in life (Back & Miller, ; Dudova et al, ; Guo et al, ; Johnson, Hollis, Kochhar, Hennessy, Wolke, & Marlow, ; Joseph et al, ; Kuzniewicz et al, ; Limperopoulos et al, ; Peyton et al, ; Pritchard et al, ; Treyvaud et al, ). While antenatal administration of magnesium sulfate in women at risk for preterm delivery reduces the risk of cerebral palsy in the fetus (Crowther, Hiller, Doyle, & Haslam, ; Doyle, Crowther, Middleton, Marret, & Rouse, ; Gano et al, ; Rouse et al, ), limited treatment options are currently available to protect preterm infants against diffuse WMI. Moreover, the mechanisms underlying diffuse WMI are not completely understood (van Tilborg et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Randomized controlled trials have subsequently confirmed these results and a recent meta‐analysis demonstrated that the frequency of CP or moderate/severe motor disability was reduced by ∼30% by antenatal MgSO 4 (Doyle et al, 2009). Furthermore, the rate of echolucent and echodense brain lesions (Hirtz et al, 2015) as well as cerebellar hemorrhages (Gano et al, 2016) has been shown to be attenuated by antenatal MgSO 4 treatment.…”
Section: Introductionmentioning
confidence: 99%